Finite element modelling of shear critical glass fibre-reinforced polymer (GFRP) reinforced concrete beams. (2nd January 2021) - Alam, Md Shah; Hussein, Amgad
ABSTRACT: Due to the different properties of GFRP bars, the available finite element packages for modelling shear critical GFRP reinforced members are questionable. This paper presents a three-dimensional (3D) nonlinear finite element analysis (FEA) model for shear critical glass fibre-reinforced polymer (GFRP) reinforced concrete beams. The beams were reinforced in longitudinal direction and there was no shear reinforcement. The FEA were carried out using concrete damage plasticity model in ABAQUS along with suitable constitutive model for concrete. Perfect bond was assumed between concrete and GFRP reinforcement. A generalized bi-linear tension stiffening model, based on the strain energy density, was used to model the contact between the concrete and GFRP bars. The FEA results were compared with the test results of GFRP reinforced beams. The robustness of the model was investigated for three different parameters: depth of beam, shear span to depth ratio, and concrete strength. The results obtained from FE analysis were analyzed for its load-deflection behaviour, crack patterns, ultimate loads; and the FE results were also compared with the test results. The comparison reveals that the model predicts the behaviour of shear critical GFRP reinforced concrete beams with reasonable degree of accuracy. Abbreviation : Glass Fibre Reinforced Polymer (GFRP)